Youth in international agricultural research for development: A background paper - Thorsen, Dorte; Glover, Dominic; Cabral, Lidia (CGIAR GENDER Impact Platform, 2024)
Youth is recognized as a key demographic in international agricultural and rural development. Although urbanization may absorb some of the youth population, agrifood systems will provide significant employment in the foreseeable future, notably in rural and peri-urban areas (Girard 2023; Dolislager et al. 2021). Young men and women hold large stakes in the future of sustainable agrifood systems, and they are recognized as an important target group for agricultural research for development (AR4D) interventions. How then should the organizations that conduct and implement AR4D projects and programs engage with youth? How should these organizations orient themselves to include youth in the research process and be sensitized to their needs and priorities? How can they conduct research, and design and develop new technologies, in ways that take into account the different needs and capabilities of youth, as well as the social positions from which they act? How can AR4D activities be organized and focused to generate substantial benefits for youth?